Effects of food and rearing density of hybrid grouper (♂ \(E. lanceolatus\) x ♀ \(E. fuscoguttatus\)) from fry stage to fingerling - Truong Quoc, Thai; Nguyen Van , Dung; Nguyen Khac , Dat; Nguyen Thi , Thu Hang (Vietnam Journal of Marine Science and Technology, 2021)
The study on the effects of food and rearing density of hybrid grouper (♂ E. lanceolatus × ♀ E. fuscoguttatus) from fry stage to fingerling was conducted at Nha Trang Mariculture Research and Development Center (Research Institute for Aquaculture No. 3) from March to May 2018 to assess the effects of live food and fish rearing density on the survival rate, the growth in length, the level of coefficient CVL and deformative rate. The study showed that feeding rotifers were better than the oyster larvae food, or the combination of rotifers and oyster larvae when used as food for the hybrid grouper at the fry stage to fingerlings with the survival rate at 5.4 ± 0.3%, specific growth rate at 7,90 ± 0,05% body length/day and the deformative ratio at 0.9 ± 0.3% (p < 0.05). Meanwhile, the rearing density of 8 fish/L to 12 fish/L of rearing water was recorded to be better than the density of 16 fish/L (p < 0.05).